2010
DOI: 10.1007/s00405-010-1250-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Epworth Sleepiness Scale with respiratory sleep parameters in patients with sleep-related breathing disorders and upper airway pathology

Abstract: The aim of the study was to test whether a correlation between the Epworth Sleepiness Scale (ESS) and respiratory sleep parameters recorded by polysomnography (PSG) in patients with sleep-related breathing disorders and upper airway pathology exists. The PSG records of 130 patients (average age 52.6 +/- 10.7 years) with upper airway pathology suspected of having obstructive sleep apnea (OSA) have been retrospectively evaluated. Upper airway pathology included deviation of the nasal septum, inferior nasal turbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
23
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 16 publications
5
23
0
7
Order By: Relevance
“…Compared to no EDS patients, EDS patients exhibited a greater AHI [1,[10][11][12], though not wholly agreed [2]. Recent study showed no correlation between the ESS and the AHI, ODI, and minimum SpO 2 in patients with upper airway pathology [7]. Our data also showed no correlation between the ESS and the AHI, ODI in OSA patients, but significant difference in AHI and ODI was found between the patients with and without EDS.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Compared to no EDS patients, EDS patients exhibited a greater AHI [1,[10][11][12], though not wholly agreed [2]. Recent study showed no correlation between the ESS and the AHI, ODI, and minimum SpO 2 in patients with upper airway pathology [7]. Our data also showed no correlation between the ESS and the AHI, ODI in OSA patients, but significant difference in AHI and ODI was found between the patients with and without EDS.…”
Section: Discussionsupporting
confidence: 51%
“…The controversies could be due to the following factors. Firstly, the EDS is determined by multiple physiologic or pathologic conditions [7]. Secondly, EDS in OSA patients measured by ESS, a self-assessment method, is not objective but may depend on the subjective personality of the patients [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die ESS wird häufig als Verlaufsparameter für Therapieerfolge eingesetzt. Für das Screening von Patienten mit OSA konnten jedoch keine befriedigenden Ergebnisse erzielt werden[2,25].Weitere einfache Screeningverfahren beinhalten die Messung der nächtlichen Oxymetrie. In einem Kollektiv von Patienten mit hoher Prävalenz an OSA konnte die alleinige Messung der nächtli-chen Oxymetrie das Vorliegen einer relevanten Schlafapnoe mit einer Sensitivität von 98% bei einer Spezifität von 48% erkennen[21].…”
unclassified
“…Similarly other deformities e.g., macroglossia, high tongue base, high arched palate, enlarged tonsils, and adenoids, submental fat, etc. also adds to the risks of obstructive sleep apnea [2,3]. Few studies suggest that craniofacial and nasopharyngeal abnormalities may be related to the severity of obstructive sleep apnea [4,5].…”
Section: Introductionmentioning
confidence: 99%